Sol-gel synthesis of 8 nm magnetite (Fe3O4) nanoparticles and their magnetic properties - Lemine, OM; Omri, K; Zhang, B; El Mir, L; Sajieddine, M; Alyamani, A; Bououdina, M (Superlattices and microstructures, 2012)
Magnetite (Fe3O4) nanoparticles were successfully synthesized by a sol-gel method. The obtained nanoparticles were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy dispersive analysis by X-ray (EDAX), transmission electron microscopy (TEM), superconducting quantum interference device (SQUID) and Moessbauer spectrometry. XRD and Moessbauer measurements indicate that the obtained nanoparticles are single phase. TEM analysis shows the presence of spherical nanoparticles with homogeneous size distribution of about 8 nm. Room temperature ferromagnetics behavior was confirmed by SQUID measurements. The mechanism of nanoparticles formation and the comparison with recent results are discussed. Finally, the synthesized nanoparticles present a potential candidate for hyperthermia application given their saturation magnetization.